CARD11 is dispensable for homeostatic responses and suppressive activity of peripherally induced FOXP3+ regulatory T cells. Issue 8 (26th June 2019) - Policheni, Antonia; Horikawa, Keisuke; Milla, Liz; Kofler, Jennifer; Bouillet, Philippe; Belz, Gabrielle T; O'Reilly, Lorraine A; Goodnow, Christopher C; Strasser, Andreas; Gray, Daniel HD
Abstract: FOXP3 + regulatory T (Treg) cells are essential for immunological tolerance and immune homeostasis. Despite a great deal of interest in modulating their number and function for the treatment of autoimmune disease or cancer, the precise mechanisms that control the homeostasis of Treg cells remain unclear. We report a new ENU‐induced mutant mouse, l acko fco stimulation ( loco ), with atopic dermatitis and Treg cell deficiency typical of Card11 loss‐of‐function mutants. Three distinct single nucleotide variants were found in the Card11 introns 2, 10 and 20 that cause the loss of CARD11 expression in these mutant mice. These mutations caused the loss of thymic‐derived, Neuropilin‐1 + (NRP1 + ) Treg cells in neonatal and adult loco mice; however, residual peripherally induced NRP1 − Treg cells remained. These peripherally generated Treg cells could be expanded in vivo by the administration of IL‐2:anti‐IL‐2 complexes, indicating that this key homeostatic signaling axis remained intact in CARD11‐deficient Treg cells. Furthermore, these expanded Treg cells could mediate near‐normal suppression of activated, conventional CD4 + T cells, suggesting that CARD11 is dispensable for Treg cell function. In addition to shedding light on the requirements for CARD11 in Treg cell homeostasis and function, these data reveal novel noncoding Card11 loss‐of‐function mutations that impair the expression of this critical immune‐regulatory protein. Abstract : We report a new ENU‐induced mutant mouse, l acko fco stimulation ( loco ), with atopic dermatitis and Treg cell deficiency typical of Card11 loss‐of‐function mutants. Interestingly, these mutations were in noncoding regions of Card11, and caused the loss of thymic‐derived, Neuropilin‐1 + (NRP1 + ) Treg cells in neonatal and adult loco mice. However, residual peripherally induced NRP1 − Treg cells remained and we showed that these cells responded normally to IL‐2 and suppressed T‐cell responses.